Decoding microbial carcinogenic strategies: ubiquitination and SUMO modification - Liu, Yue; Zeng, Xianghai; Lyu, Zhimai; Huang, Dandan (Frontiers in Microbiology, 2025)
Carcinogenic microorganisms (including viruses, bacteria, fungi, etc.) disrupt cellular homeostasis to drive tumorigenesis by hijacking the host ubiquitin-proteasome system (UPS) and SUMOylation networks, with oncogenic viruses representing the core agents of this regulatory mechanism. Specifically: - Human papillomavirus (HPV) E6 protein binds E3 ubiquitin ligase E6AP to mediate ubiquitin-mediated degradation of tumor suppressor p53, thereby disabling cell cycle surveillance; the HBx protein of hepatitis B virus (HBV) evades its own ubiquitin-mediated degradation by inhibiting the activity of the E3 ligase SIAH1, while simultaneously upregulating DNA methyltransferases to disrupt host epigenetics; the core protein of hepatitis C virus (HCV) induces methylation of the E6AP promoter, blocking its own ubiquitin-mediated degradation to maintain oncogenic activity; Epstein–Barr virus (EBV) LMP1 activates IRF7 via K63-linked ubiquitination, sustaining NF-xB pathway activation to promote proliferation; Kaposi’s sarcoma-associated herpesvirus (KSHV) K3 protein mediates MHC-I molecule ubiquitination-dependent endocytosis, achieving immune evasion. Furthermore, non-viral microorganisms such as Helicobacter pylori CagA and aflatoxin A also participate in carcinogenesis by regulating the UPS/SUMO system. In summary, targeted modulation of the UPS/SUMO system constitutes a core oncogenic strategy for carcinogenic microorganisms (particularly viruses), providing molecular targets for precision cancer therapy.